Serum phosphorylated neurofilament heavy subunit levels and its association with the risk for catastrophic injury in thoroughbred racehorses - Rojas-Nunez, I.; Gomez, A. M.; Palmer, S.; Mohammed, H. O. (Journal of Equine Veterinary Science, 2022)
Neurofilaments are structural proteins that are concentrated in the body and axons of neurons. Damage to the neurons or axons as a result of trauma or infectious diseases leads to the release of neurofilaments into blood and cerebrospinal fluid (CSF). This case-control study was carried out to compare serum levels of phosphorylated neurofilament heavy chain (pNF-H) between clinically healthy Thoroughbred (TB) horses and TB horses that suffered catastrophic musculoskeletal injuries (cMSI), and to investigate the correlation between putative risk factors and serum concentrations of pNF-H in injured horses. Blood samples were collected from clinically healthy horses and from horses that suffered cMSI. The concentration of pNF-H in serum samples was determined using the Phosphorylated Neurofilament H Sandwich enzyme-linked immunosorbent assay kit. A total of 343 horses were enrolled in the study (148 cases and 195 controls). The median serum concentration of pNF-H for controls was 0.0 ng/ml and for cases was 0.07 ng/ml. No significant difference was observed between the 2 groups in racing. The number of lifetime starts was correlated with serum pNF-H concentration in case horses. The serum concentration of pNF-H was higher in case horses that experienced cMSI while training than while racing. The number of lifetime starts is a proxy measure for several risk factors related to cumulative exercise load during the career of racehorses. Measurement of serum concentrations of pNF-H in TB racehorses does not support the hypothesis that subclinical neurologic injury or conditions are associated with catastrophic injury of TB racehorses.